Good Village Governance: A Framework for Simulacra and Hyperreality in Village Finance Management - Ramadhan, Puja Rizqy; Suwarno; Pratiwi, Shella (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to review the concept of good village governance based on Jean Baudrillard's perspective on the concept of simulacra and hyperreality. This study uses primary data obtained from observations and interviews with informants. The research approach used is a qualitative method. The study consists of data collection procedures, data presentation, data reduction and drawing conclusions. The results of the study indicate that the concept of Good Village Governance has the potential to lead society to a state of hyperreality, where real and apparent reality are difficult to distinguish. This situation also causes information to be more easily manipulated, something that village officials must be aware of in their role in managing finances. At a time when globalization and the impact of modernity are unavoidable, it is time for village officials to strengthen the elements of professional ethics, moral culture, spirituality, so as to be able to create professional village officials who are also able to become role models in the midst of society.